Tanzania : The Story of an African Transition - Nord, Roger; Dunn, David G.; Hajdenberg, Alejandro; Sobolev, Yuri. (Washington, D.C. : International Monetary Fund, 2009)
This volume documents Tanzania's remarkable turnaround from severe economic distress in 1985, and reviews the economic policies that twenty years later contributed to a successful reversal. Tanzania still faces many policy and reform challenges, despite the many recent economic achievements the country has experienced.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet